3D prism shaped circularly polarised MIMO diversity antenna with 360o angular coverage. Issue 4 (2nd October 2022) - Chaudhary, Prashant; Kumar, Ashwani; Patel, Kamlesh; Arya, Ravi Kumar; Ali, Maifuz; Verma, A.K.
ABSTRACT: This paper presents the 3D prism-shaped circularly polarised MIMO Diversity Antenna with 360° angular coverage. The proposed antenna has six elements, and it covers the X-band with impedance matching from 8.0 to 11.8 GHz (38.4%), 3 dB axial ratio from 8.05 to 10.6 GHz (27.34%). A metallic copper cylinder is placed inside the prism to improve the isolation and axial ratio. All the antennas are highly isolated, with isolation is more diminutive than −20.5 dB, except the adjacent element to the edge of the prism, for which it is −14.7 dB. The Envelope Correlation Coefficient (ECC) is less than 0.035. The proposed antenna structure shows the pattern or angle diversity in the whole 360° angle with polarisation diversity.